2012
DOI: 10.4236/fns.2012.311208
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Nutritional and Toxicological Analyses of Leaves and Fruits of <i>Solanum macrocarpon</i> Linn (Solanaceae) in Cotonou (Benin)

Abstract: Vegetables are very important sources of protein and minerals. Some of them even have medicinal properties recognized traditionally. Despite the large number of studies carried out on various vegetables and vegetable crops, very few have scientifically explored the usefulness of S. macrocarpon. This study identified the main groups of chemicals and mineral elements to explain any medicinal or nutritional value. It has also identified some toxic elements contained in this vegetable. Phytochemical screening was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
2
20
1
Order By: Relevance
“…The increment in the protein content of the enriched bread could be attributed to high protein content in dried vegetable powders. Dried fluted pumpkin, African eggplant, and amaranth leaves' powders have been reported to contain 31.7, 27.2, and 23.6% protein, by Kajihausa et al [24], Dougnon et al [25], and Udousoro and Ekanem [26], respectively.…”
Section: Sensory Evaluation Of Vegetable Enriched Breadsmentioning
confidence: 99%
“…The increment in the protein content of the enriched bread could be attributed to high protein content in dried vegetable powders. Dried fluted pumpkin, African eggplant, and amaranth leaves' powders have been reported to contain 31.7, 27.2, and 23.6% protein, by Kajihausa et al [24], Dougnon et al [25], and Udousoro and Ekanem [26], respectively.…”
Section: Sensory Evaluation Of Vegetable Enriched Breadsmentioning
confidence: 99%
“…However, there are different types of species and selection in the genus that have diverse shape, size and colour. While information is available on phenolic contents, flavonoids, anthocyanins, antioxidants, and anti-diabetic activity of Solanum melongena eggplant fruit extract (kwon et al, 2008;Scalzo et al, 2010), few information are reported for Solanum macrocarpon which is commonly found in southwestern Nigeria known as "igbagba pupa", and used as sauce, stew and part of salad, but there are information on the leaf part which is been used as soup condiment in Nigeria (Oboh et al, 2005;Fasuyi, 2006;Ijarotimi et al, 2010), while the aqueous extract of the fruit had been shown to be nutritious, to lower high blood pressure, to treat constipation and lower hyperlipidaemia (Chinedu et al, 2011;Dougnon et al, 2012;Sodipo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The alkaloids are present in the extracts of leaves but absent in those of flowers while the steroids and the combined anthracene C-heterosides are presents in the extracts of flowers but absent in those of leaves. Such differences of phytochemical composition was reported by Dohou et al (2003) on various organs (Leaves, flowers, roots, peel and fruits) of Thymelaea lythroides, Dougnon et al (2012) on fruits and leaves of Solanum macrocarpum and Tsiba et al (2010) in Congo on the essential oils of leaves, flowers, roots, and stems of Lippia multiflora itself.…”
Section: Phytochemical Screeningmentioning
confidence: 81%
“…They regulate carbohydrate and protein metabolism, increase muscles and bone synthesis and are also associated with hormonal control in women (Hossain et al, 2013). Mucilage (soluble fibres) also has several medicinal properties (Dougnon et al, 2012;Adjatin et al, 2013;Agbaire et al, 2013;Simons, 2013). It is anti-cholesterol (aid to lower cholesterol in the blood), anti-constipation (helps to prevent the appearance of intestinal decomposition), anti-cancer, anti-diabetic agents and stomachic (has ability to protect internal mucous membranes).…”
Section: Phytochemical Screeningmentioning
confidence: 99%